Patient Selection Criteria For Off-Pump and On-Pump Coronary Artery Bypass Grafting (Annals of Medical Research, 2021)
None
Keywords: Off-Pump Coronary Bypass; On-Pump Coronary Bypass; Myocardial Ischeamia.